2018
DOI: 10.1111/1462-2920.14313
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal succession of small planktonic eukaryotes inhabiting surface waters of a coastal upwelling system

Abstract: Small eukaryotes (0.2-20 μm cell-size) represent a significant fraction of the microbial plankton community in shelf waters of NW-Spain. The community composition of small eukaryotes living at the surface and at the base of the photic zone was analysed by means of 18S rDNA high-throughput sequencing on a circa-monthly basis over a 23 months period. Ostreococcus was the most abundant taxon in surface waters, showing marked peaks in read abundance in spring and late summer, while Syndiniales dominated at the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 112 publications
6
52
1
Order By: Relevance
“…High amount of negative interactions is generally interpreted as the result of functional heterogeneity, direct competition for limiting resources or interactions like predator-prey relations or allelopathy (Long and Azam, 2001). However, positive or negative ecological interactions may simply reflect co-occurrence or non-coexistence patterns among populations (Hernández-Ruiz et al, 2018). Particularly in this study negative interactions may just derive from the spatial and temporal ecological niche partitioning, which matches all other results that point to different communities characterizing the two ecosystems in the different seasons.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…High amount of negative interactions is generally interpreted as the result of functional heterogeneity, direct competition for limiting resources or interactions like predator-prey relations or allelopathy (Long and Azam, 2001). However, positive or negative ecological interactions may simply reflect co-occurrence or non-coexistence patterns among populations (Hernández-Ruiz et al, 2018). Particularly in this study negative interactions may just derive from the spatial and temporal ecological niche partitioning, which matches all other results that point to different communities characterizing the two ecosystems in the different seasons.…”
Section: Discussionsupporting
confidence: 72%
“…In the interpretation of network properties, the ecological role of hub species is still unclear. In several studies, hubs are often proposed to be critical or keystone components for network (Peura et al, 2015;Comte et al, 2016;Hernández-Ruiz et al, 2018) but a recent study has also demonstrated that known keystone species do not necessarily result in detectable signals in co-occurrence networks (Freilich et al, 2018). In our study, most hubs were not dominant in abundance, suggesting that scarcely abundant but highly connected OTUs could play an important role in network dynamic and stability not only in marine communities (Xue et al, 2018) but also in the lagoon habitat.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The matrix of MIC values corresponding to a p-value < 0.01, based on pre-computed p-values of various MIC scores at different sample sizes, was used (MIC > 0.68 in this case) in order to visualize networks of species' associations with Cytoscape 3.5.1 [32]. We identified the negative or positive type of relationship between each pair of species included in the network according to Hernández-Ruiz et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, OTUs having a single peak of abundance per year could be the norm across microbial assemblages in surface ocean temperate waters. This does not have to be the case for the whole water column, as it has been observed that seasonality is attenuated at deeper waters (Hernández-Ruiz et al, 2018;Kim et al, 2014).…”
Section: Quantifying Community Seasonality and Recurrencementioning
confidence: 99%